Gazing over Chaos: Panoptic Reflections of Gotham and the Failure of the Dispositive - Marko Lukić ([sic])
NOTE: Due to a possible editorial conflict of interest the author did not participate in the editing/publishing process of this issue of the journal.What this analysis proposes is a reevaluation of the crucial, and often neglected, issues of space/place within the Batman opus, concentrating primarily on Batman’s use of various spaces/places in order to enforce control and/or discipline. The study will initially be premised on the use of the Foucauldian discourse regarding the implementation of invisible control and therefore power, structuring its arguments around the theoretical concepts of the dispositive/apparatus as well as Bentham’s Panopticon. The paper will develop the idea of the Batcave as the actual site of control, the starting point of the Foucauldian notion of the “gaze being alert everywhere” (Discipline and Punish 195). Symbolically made visible by the prominent brightness of the Bat-signal, but nevertheless constantly hidden from the eyes of the criminals, the Batcave assures the presence of power that “should be visible and unverifiable” (Foucault, Discipline 201), and therefore exerts discipline. The paper will also address the issue of Crime Alley as a site of inversion by using the theoretical concept of heterotopian space as proposed by Foucault, as well as Gaston Bachelard’s idea of subjective/domestic spaces. Following the idea of a space recoded by tragedy, the analysis will explore the immunity of Crime Alley in relation to Batman’s disciplinary praxis and the Panoptic gaze, as well as its potential to subvert Batman’s “laboratory of power” (Foucault, Discipline 204).